Hubungan Kompetensi Profesional Guru Pendidikan Agama Kristen dan Budi Pekerti Dengan Hasil Belajar Siswa Kelas VII SMP Negeri 1 Balige Tahun Pembelajaran 2024/2025 - Sagita Nova Sianipar; Maria Widiastuti; Helena Turnip; Johari Manik; Tiurma Barasa (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to determine the extent of the positive and significant relationship between the professional competence of Christian Religious Education (CRE) teachers and the learning outcomes of class VII students at SMP Negeri 1 Balige in the 2024/2025 academic year. This research uses a quantitative method with a descriptive inferential approach. The population of the study consists of all class VII students of SMP Negeri 1 Balige, totaling 149 students. The sampling method used is random sampling, with a sample size of 54 students. The research instruments used are a closed questionnaire to measure the professional competence of teachers and UH (Ulangan Harian or Daily Test) scores to measure student learning outcomes. The data analysis results show that: a) the correlation test obtained a value of rcount = 0.293, which is greater than rtable = 0.226, indicating a positive relationship between the two variables; b) the significance test yielded a value of tcount = 2.210, which is greater than ttable = 2.000, meaning the null hypothesis (H0) is rejected and the alternative hypothesis (Ha) is accepted. Based on these findings, it can be concluded that the professional competence of CRE teachers has a significant relationship with student learning outcomes. Therefore, improving teachers’ professional competence is expected to enhance student learning outcomes. This study contributes to the development of education and can serve as a reference for teachers and schools to improve the quality of teaching.